2019
DOI: 10.1007/s10518-019-00749-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamic behaviour of severely corroded reinforced concrete columns: shaking table study

Abstract: A set of benchmark, medium scale, shaking table tests on corroded reinforced concrete (RC) columns is conducted with the aim of investigating the effects of corrosion damage on the nonlinear dynamic behaviour of RC bridge piers. The experimental programme consists of an uncorroded control specimen and two corroded RC column specimens, with identical structural details. An accelerated corrosion procedure is used to corrode the RC columns. The uncorroded and corroded specimens are subjected to far-field long dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In this section, only a summary of the experimental results is provided. The detailed discussion of experimental results and structural damage are beyond the scope of this paper and are reported in different publications (Ge et al, 2019;Kashani, Ge, et al, 2019). The FF-LC-Corr1 specimen failed after 10s in the extensive (300%) damage level test.…”
Section: Shaking Table Experimental Testing and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, only a summary of the experimental results is provided. The detailed discussion of experimental results and structural damage are beyond the scope of this paper and are reported in different publications (Ge et al, 2019;Kashani, Ge, et al, 2019). The FF-LC-Corr1 specimen failed after 10s in the extensive (300%) damage level test.…”
Section: Shaking Table Experimental Testing and Resultsmentioning
confidence: 99%
“…In order to investigate the seismic behaviour of uncorroded and corroded RC bridge piers in terms of the effects of ground motion characteristics, structural detailing and corrosion levels, a series of shaking table tests are conducted on six large-scale RC columns. The experimental campaign is included four uncorroded and two corroded columns (Ge et al, 2019;Kashani, Ge, et al, 2019). The columns with cross-sections of 250mm×250mm are cast in a 1500mm × 700mm × 300mm foundation.…”
Section: Shaking Table Experimental Testing and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several shake table experiments on cantilever RC columns have been performed by positioning the inertial mass directly on top of the specimen's head and subjecting it to the earthquake ground motion record. Examples of such studies can be found in the works by Mosalam et al [12], Sakai et al [13], Schoettler et al [6], and Ge et al [14]. In this configuration, the axial force on the column model generated by the superstructure weight and the P-Δ effect can be replicated.…”
Section: Inertial Mass Supported By the Specimenmentioning
confidence: 96%